Ultimate Spider-Man web-warriors. Spider-verse. #4 - Caramagna, Joe (Abdo Spotlight, 2020)
Spider-Man and the Web-Warriors--Spider-Men from alternate dimensions--all converge to battle the Spider-Goblin.